(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
The employees as the main component in an organization have a very important role to determine the success of the organization’s gools. Because of the importance of them to reach the goals. They should have good competence, responsibility, independence, creativity and spirit to plan and to do the programs which are planned by the organization. The organization often get difficultiesin providing human resources. There are many problems because of the lack of good human resources. They impact to reach the goals of the organization.The goals of this research are to identify the factors of unoptimal employee performance, to analyze the factors that cause unoptimal employee performance, to evaluate the factors of unoptimal employee performance, and to find the solution to solve the problems to improve the employee performance of Dinas Kepemudaan dan Olah Raga dan Pariwisata. To search the factors cousing unoptimal employee performance will be started by identifying them of Dinas Kepemudaan dan Olah Raga dan Pariwisata, analyzing them, evaluating them and solving them to improve optimal employee performance. The other hand, it searchesbiography characteristic, individual characteristic, and the perception of the employees. The result of employee performance will be evaluated by SKP and Perilaku Kerja.